Effects of soil profile on the transient performance of substation grounding system - Zulkurnain Adul Malek; Mohammad Shahrin Affendy Yaman; Muhammad Adnan (Institute of Advanced Engineering and Science, 2020)
Lightning transient characteristic of the grounding grid is fundamental for optimum performance of lightning protection of a substation. In order to design an appropriate grounding system for such substation, it is important to study its transient characteristics because the high impulse current is significantly different compared to power frequency current. In this paper, substation grounding grid model was developed using CDEGS software to analyze the grid transient performance in terms of ground potential rise (GPR), touch voltage and step voltage when the grounding system is struck by a lightning impulse current. Several parameters, such as lightning current amplitude, feed point and the number of sub-grids, were altered to study their relationship with the transient performance. The maximum transient GPR, touch voltage, and step voltage increase as the lightning current amplitude increase. The maximum transient GPR and step voltage are the highest at the corner of the grounding grid while the maximum touch voltage is the highest at the centre of the grounding grid. In addition, the maximum transient GPR and step voltage decrease when the number of sub-grid increases. In contrast, the touch voltage slightly increases as the number of sub-grid increases. The maximum transient GPR, and step voltage are the highest at the 2-layer and the lowest at the uniform soil or single-layer soil.